Spectral Doppler assessment of middle uterine artery hemodynamics across the estrous cycle in Tharparkar cows - Sahu, Uttam Kumar; Kumar, Brijesh; Khan, M. H.; Singh, Mayank; Warghat, Chinmay; Kharayat, Nitish Singh; Reddy, Athidi Lokavya; Yadav, Vandana; Chouhan, V. S.; Sahu, Laxmi; Kumar, Mahesh; Rajput, Piyush; et al. (Frontiers in Animal Science, 2026)
IntroductionBreed-specific characterization of uterine hemodynamics is essential for improving reproductive monitoring and management in indigenous Bos indicus cattle; however, systematic Doppler reference data across the estrous cycle remain limited. This study aimed to evaluate cyclic changes in middle uterine artery (MUA) blood flow and its association with luteal function in Tharparkar cows using transrectal spectral Doppler ultrasonography.MethodsTen clinically normal, cyclic Tharparkar cows (parity 1–3) were examined at three-day intervals from estrus (D0) to the subsequent estrus (D21). Doppler parameters including resistance index (RI), pulsatility index (PI), time-averaged maximum velocity (TMAX), vessel diameter, and calculated blood flow volume (BFV) were recorded. Follicular dynamics, corpus luteum (CL) size, and serum progesterone (P4) concentrations were assessed concurrently.ResultsReproductive characteristics were consistent with Bos indicus physiology, with a mean preovulatory follicle diameter of 13.14 ± 0.31 mm, luteal phase length of 16.10 ± 0.23 days, and estrous cycle length of 20.50 ± 0.30 days. CL size showed a strong positive correlation with serum P4 concentrations (r = 0.86, P < 0.05), confirming functional luteal competence. All Doppler indices exhibited significant cyclic variation across the estrous cycle (P < 0.05). RI and PI were lowest at estrus, increased during early luteal development, peaked during the mid-luteal phase (D9–D12), and declined toward the subsequent estrus. RI showed positive correlations with serum P4 (r = 0.73, P < 0.05) and CL size (r = 0.52, P < 0.05). In contrast, TMAX, BFV, and MUA diameter displayed reciprocal trends, with maximum values at estrus and minimum values during the mid-luteal phase. BFV correlated positively with TMAX (r = 0.84, P < 0.05) and vessel diameter (r = 0.70, P < 0.05), and negatively with RI (r = −0.58, P < 0.05) and P4 (r = −0.65, P < 0.05).DiscussionThis study establishes novel, breed-specific uterine artery Doppler reference profiles for Tharparkar cows, demonstrating distinctive cyclic vascular regulation closely linked to luteal function. These findings support Doppler ultrasonography as a functional tool for estrus confirmation, luteal assessment, and fertility monitoring in indigenous cattle.